PENGARUH INNOVATION CAPABILITY TERHADAP FINANCIAL PERFORMANCE MELALUI BRAND EQUITY SEBAGAI VARIABEL INTERVENING PADA INDUSTRI PERHOTELAN DI SURABAYA - Stella Lovinanda (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of innovation capability to brand equity; brand equity to financial performance; and innovation capability to financial performance in hospitality industries in Surabaya. This study also examine the indirect and significant relationship of innovation capability to financial performance through brand equity as intervening variable in hospitality industry in Surabaya.This study used a quantitative approach, and the data were obtained by distributing questionnaires to hospitalities industries in Surabaya and processed by using smartPLS software. This study showed that there was positive and then significant relationship of innovation capability to brand equity; brand equity to financial performance; and innovation capability to financial performance in hospitality industries in Surabaya. But, brand equity was inadequate to become an intervening variable between innovation capability and financial performance because the direct relationship between innovation capability and financial performance gave greater affect than if it was through brand equity.